Monocyte Trajectories Endotypes Are Associated With Worsening in Septic Patients - Bodinier, Maxime; Peronnet, Estelle; Brengel-Pesce, Karen; Conti, Filippo; Rimmelé, Thomas; Textoris, Julien; Vedrine, Christophe; Quemeneur, Laurence; Griffiths, Andrew D.; Tan, Lionel K.; Venet, Fabienne; Maucort-Boulch, Delphine; et al. (Frontiers in Immunology, 2021)
Sepsis is a life-threatening organ dysfunction caused by a dysregulated host response to infection. The immune system plays a key role in sepsis onset and remains dysregulated over time in a heterogeneous manner. Here, we decipher the heterogeneity of the first week evolution of the monocyte HLA-DR (mHLA-DR) surface protein expression in septic patients, a key molecule for adaptive immunity onset. We found and verified four distinctive trajectories endotypes in a discovery (n = 276) and a verification cohort (n = 102). We highlight that 59% of septic patients exhibit low or decreasing mHLA-DR expression while in others mHLA-DR expression increased. This study depicts the first week behavior of mHLA-DR over time after sepsis onset and shows that initial and third day mHLA-DR expression measurements is sufficient for an early risk stratification of sepsis patients. These patients might benefit from immunomodulatory treatment to improve outcomes. Going further, our study introduces a way of deciphering heterogeneity of immune system after sepsis onset which is a first step to reach a more comprehensive landscape of sepsis.